Internalization of Humanist-Religious Education in Child-Friendly Madrasahs in Indonesia - Subqi, Imam; Hariyadi, Rahmat; Zaman, Badrus; Sutrisno, Sutrisno (Universitas Muhammadiyah Magelang, 2022)
The large number of violence cases in educational institutions by educators to students or by student to student as the result of the lack of sense of humanity makes education unfriendly. Therefore, an orientation in instilling humanist-religious education is needed. The objective of this study is to explore the internalization of humanist-religious education through planning, implementation, and evaluation of child-friendly madrasah (Islamic school). First, the planning of humanist-religious education internalization can be formulated in forms of socialization on children rights and protection, mapping of madrasah condition, preparation of related policies, and child-friendly madrasah team organization. Second, the process of humanist-religious education internalization can be done through customization and exemplary. Last, the evaluation components of humanist-religious education in child-friendly madrasah include context evaluation, inputs, process, and products. The result: this study can be used as the reference for madrasah policies.